An Analysis of Students’ Errors in Using Simple Past Tense in Translating Narrative Text - Devie Reztia Anjarani; Rohmah Indahwati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2019)
Error may appear when students put the English grammatical incorrectly. Errors is mostly occurred in English as the foreign or second language. The aim of this study is describing kinds of errors are made by the seventh semester students of English department in Madura University on the use of simple past tense in a translated narrative text. The research method used in this study is descriptive qualitative. The subject is seventh semester students of English department which consist of 15 students. The instruments used is translating test. The data is analyzed by collecting the data from students, identifying the errors based on its grammatical errors, classifying them into errors classification, and calculated them into percentage. The results showed that the students' errors can be classified into four kinds of errors, which are 25% for omission errors, 5.36% for addition errors, 62.5% for missed formation errors, and 7.14% for missed ordering errors. There are total 56 errors occurred which is dominated by missed ordering errors. The teachers recommended to make a clear understanding related to differentiate grammatical differences between Indonesia and English. Further, students need to practice it more often. The other researchers can provide techniques to increase students’ English grammatical understanding, especially in simple past tense usage.